Social Capital of Micro, Small and Medium Enterprises in Kampung Purun for Improving Entrepreneurship Education - Herry Porda Nugroho Putro; Rusmaniah Rusmaniah; Mutiani Mutiani; Ersis Warmansyah Abbas; Jumriani Jumriani; Muhammad Ridha Ilhami (STAI Hubbulwathan Duri, 2022)
This study aims to analyze micro, small and medium enterprises (MSMEs) in society to improve entrepreneurship education at the higher education level. The case study method is used to describe how relevant the social capital of MSMEs in Kampung Purun is to be integrated into entrepreneurship education in higher education. The data analysis technique used the interactive model of Miles and Huberman. Meanwhile, the researcher used the triangulation technique to get the saturation of research data. The results of the study describe that social capital that appears in MSMEs in Kampung Purun includes; beliefs, norms, and networks, are described, among others; 1) Trust that creates a culture of transparency or openness can increase accountability, strengthen responsibilities and lead to better decisions; 2) Norms related to social values, cooperation, concern, and tolerance; and 3) a social network that is bound by family relationships between craft business groups. These three elements of social capital directly become a sustainable relationship between craftsmen. Based on the elements of social capital, this shows the harmony in the practice of entrepreneurship education in the Social Studies Education Study Program, FKIP, Lambung Mangkurat University. The alignment of social capital in MSMEs in Kampung Purun and entrepreneurship education can be divided into two: First, internal social capital that creates and distributes attitudes, norms, and traditions; Second, external social capital is directly related to the use of products and partners.